The change of tissue of inhibitor metalloproteinase 1 (timp-1) after rosella (hibiscus sabdariffa) extract gel application on artificial crown patients with gingivitis - Lenni I. Hatta; Mochammad Dharmautama; Maqhfirah Amiruddin; Ike D. Habar (Journal of Dentomaxillofacial Science, 2019)
Objective: This study was to investigate the increase of TIMP-1 Gingival Clavicular Fluid after application of rosella flower extract gel on gingiva as the standard treatment of gingivitis after insertion of acrylic crown.Material and Methods: This research Type is pure experimental research using randomized design on pre- and post-t-test with control group (The randomized pretest-posttest control group design). Clinical test (in vivo test) were done to value the effect gel therapeutic containing Rosella extract as therapy on standards gingivitis treatment in patients with artificial crownResults: Antimicrobial test of Rosella flower extract on P. gingivalis and S. Sanguis bacteria showed that antimicrobial effectiveness of Rosella flower extract was found at concentration of 10%.Conclusion: 10% Rosella gel extracts can be used asone alternative ingredients in standard gingival inflammation treatment due to artificial acrylic crown using